The Effect of B - Lynch Compression Suture on Fertility Potential - Akpınar, Funda; Güvendağ Güven, Seda; Üstüner, Işık (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: To investigate the potential complications like intrauterine synechia and tubal occlusion following B- lynch suture which was used to control the postpartum hemorrhage. STUDY DESIGN: Between December 2010 and December 2011 at the Department of Obstetrics and Gynecology, Rize Education and Reseach Hospital, 8 patients underwent B lynch suture for postpartum hemorrhage that was intractable to medical treatment and needed blood transfusion. These patients were called at 3. month of postpartum period. Uterine cavity and tubal patency was evaluated with hysterosalpingography and hysteroscopy. RESULTS: Early postpartum hemorrhage was controlled with B- lynch suture in all patients. In hysterosalpingographic and hysteroscopic inspection; uterine cavities were normal with bilateral tubal free passages in all patients. CONCLUSION: B- lynch suture was found to be an effective fertility preserving alternative to emergency postpartum hysterectomy in reproductive age women.